ENADE e fluxo curricular nos cursos de graduação em Ciências Contábeis no Brasil - Silva, Vanessa Ramos da (2016)
Higher Education Institutions (HEI) play an important role in the training process of the professionals who will act in society. The steps and elements present in the education system for them offered and the curriculum, which provide the development of skills and abilities of students, are structured in their Pedagogical Political Project (PPP). With the expansion of the number of students enrolled in undergraduate programs, the evaluations carried out, both of HEI as the students themselves, such as the National Exam of Student Performance (ENADE), it is important to improve the courses. The question, that provoked this study, was to determine if the HEI curricular organization that offer the course in Accounting is related to academic performance of students in ENADE the year 2012. In the literature review we discussed topics related to the Educational Production Function Theory, about the determinants of academic performance and about definitions and characterizations of academic curriculum. The research was documentary, classified as descriptive and qualitative and quantitative approach. The sample consisted of 447 Brazilian HEI who provided curriculum information. Statistical tests s realized, were: descriptive analysis, Spearman correlation, multiple linear regression test, Wilcoxon test and Mann-Whitney test. Comparing the amount of hours of classified courses as the contents of groups, with the following variables: Brazilian region; administrative category; academic organization; percentage of doctors; percentage of teachers; percentage of teachers with full working arrangements; percentage of infrastructure; percentage of didactic-pedagogical organization; note of entrants in the National Secondary Education Examination (ESMS); and the number of graduates participating in ENADE and ENADE note, it was found that the greater the hourly charges granted by HEIs for basic training content, tend to belower income students in ENADE, considering that the main focus of the evaluation are the vocational training content. Thus, institutions with more hours to professional disciplines tend to get better grades.